2014
DOI: 10.1002/smll.201402682
|View full text |Cite
|
Sign up to set email alerts
|

Ternary Sn–Ti–O Based Nanostructures as Anodes for Lithium Ion Batteries

Abstract: SnO(x) (x = 0, 1, 2) and TiO(2) are widely considered to be potential anode candidates for next generation lithium ion batteries. In terms of the lithium storage mechanisms, TiO(2) anodes operate on the base of the Li ion intercalation-deintercalation, and they typically display long cycling life and high rate capability, arising from the negligible cell volume change during the discharge-charge process, while their performance is limited by low specific capacity and low electronic conductivity. SnO(x) anodes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 91 publications
1
35
0
Order By: Relevance
“…In the first discharge cycle, the reduction peak located at about 0.85 V corresponds the irreversible transformation of SnO 2 into metallic Sn (according to the equation: SnO 2 + 4Li + + 4e -→ 2Li 2 O + Sn), while the reduction peak at 0.12 V can be attributed to the formation of Li-Sn alloys. [27,29,[34][35][36] The broad peak at 0.57 V corresponds to the de-alloying of the Li-Sn alloys, whose current increases in the following scans, indicating a possible activation process in the electrode materials.…”
Section: The Electrochemical Properties Of the Sno 2 Sno 2 -Mwcnt Andmentioning
confidence: 97%
“…In the first discharge cycle, the reduction peak located at about 0.85 V corresponds the irreversible transformation of SnO 2 into metallic Sn (according to the equation: SnO 2 + 4Li + + 4e -→ 2Li 2 O + Sn), while the reduction peak at 0.12 V can be attributed to the formation of Li-Sn alloys. [27,29,[34][35][36] The broad peak at 0.57 V corresponds to the de-alloying of the Li-Sn alloys, whose current increases in the following scans, indicating a possible activation process in the electrode materials.…”
Section: The Electrochemical Properties Of the Sno 2 Sno 2 -Mwcnt Andmentioning
confidence: 97%
“…26 Even various TiO 2 /SnO 2 composites with 1D nanostructure have been reported, few of which chose TiO 2 nanotubes as building block for material preparation. 17,26 The nanotubes…”
Section: Introductionmentioning
confidence: 99%
“…The first discharge and charge capacities of the Ti 0.74 Sn 0.26 O 2 /rGO are 1035.5 and 520.8 mA h g −1 , respectively. The voltage plateau at about 1.1 V in the first discharge curve is corresponding to several influences, involving lithium ion insertion process into rutile Ti 0.7 Sn 0.3 O 2 , electrolyte decomposition and irreversible formation of Li 2 O . In the discharge curves, the capacity of Ti 0.74 Sn 0.26 O 2 /rGO is gradually decreased in the first 10 cycles, and subsquently maintained at about 500 mA h g −1 .…”
Section: Resultsmentioning
confidence: 98%
“…Significantly, comparing to the reported heterogeneous TiO 2 ‐SnO 2 composite materials, Ti−Sn−O solid solution material distinctly showed the self‐adopted combination of components in the evenly phase, which should be a beneficial strategy to design a good candidate . In this area, Rogach and co‐workers reported that some nanocrystalline Ti−Sn−O solid solution materials exhibited the excellent structure stability as well as the high capacity . Furthermore, to obtain the high performance anode material for the application in LIBs, good electrical conductivity is also an important element.…”
Section: Introductionmentioning
confidence: 99%